Corporate financial and investment policies when future financing is not frictionless - Almeida, Heitor; Campello, Murillo; Weisbach, Michael S. (Journal of Corporate Finance, 2011)
We study a model in which future financing constraints lead firms to have a preference for investments with shorter payback periods, investments with less risk, and investments that utilize more pledgeable assets. The model also shows how investment distortions towards more liquid, safer assets vary with the marginal cost of external financing and with firm internal cash flows. Our theory helps reconcile and interpret a number of patterns reported in the empirical literature, in areas such as risk-taking behavior, capital structure choices, hedging strategies, and cash management policies. For example, contrary to Jensen and Meckling [Jensen, M., Meckling, W., 1976. Theory of the Firm: managerial behavior, agency costs, and ownership structure. Journal of Financial Economics 305–360], we show that firms may reduce rather than increase risk when leverage increases exogenously. Furthermore, firms in economies with less developed financial markets will not only take different quantities of investment, but will also take different kinds of investment (safer, short-term projects that are potentially less profitable). We also point out to several predictions that have not been empirically examined. For example, our model predicts that investment safety and liquidity are complementary: constrained firms are specially likely to decrease the risk of their most liquid investments.